OFC/NFOEC 2008 - 2008 Conference on Optical Fiber Communication/National Fiber Optic Engineers Conference 2008
DOI: 10.1109/ofc.2008.4528385
|View full text |Cite
|
Sign up to set email alerts
|

DQPSK modulation for robust optical transmission

Abstract: The feasibility of long-haul transmission using differential quadrature phase shift keying (DQPSK) modulation is discussed. We focus in particular on the trade-off between spectral efficiency and reach in optical transmission systems using DQPSK modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
1
11
0
6
Order By: Relevance
“…Both at 40-Gb/s [14,15] and 100-Gb/s [2,4] similar BER sensitivities have been reported for single carrier and OFDM transmission systems. The OSNR sensitivity for coherently detected systems is for a fixed gross data rate independent of the number of subcarriers that is used.…”
Section: Osnr Sensitivitysupporting
confidence: 77%
See 1 more Smart Citation
“…Both at 40-Gb/s [14,15] and 100-Gb/s [2,4] similar BER sensitivities have been reported for single carrier and OFDM transmission systems. The OSNR sensitivity for coherently detected systems is for a fixed gross data rate independent of the number of subcarriers that is used.…”
Section: Osnr Sensitivitysupporting
confidence: 77%
“…PMD, however, causes depolarization as well, thus in order to realize a large PMD tolerance a polarization diverse receiver is required. It has been shown that in combination with a polarization diverse receiver both single carrier [14] and multi-carrier (OFDM) [15] systems can offer a practically unlimited tolerance towards PMD.…”
Section: Chromatic Dispersion and Pmd Tolerancementioning
confidence: 99%
“…In order to focus on the label detection performance, the measurement of BER for DQPSK payload are omitted as the performance of this modulation format is well documented in the literature [9], however we checked and successfully verified that the DQPSK payload signal was error-free for both power profiles for OSNR values cases. Fig.…”
Section: Experimental Description and Resultsmentioning
confidence: 94%
“…In numerical simulations, OPC offers the best SNR of the techniques considered; this is because midpoint OPC splits the link in two, reducing the quadratic growth of parametric noise amplification, and halving the length over which the signal polarisations are decorrelated. In this section, we briefly review progress in OPC device and system development, concentrating on systems employing coherent detection [22]. OPCs have been fabricated from a wide variety of materials including fibre [23][24][25][26][27][28], bulk [29] and quantum dot [30] semiconductor optical amplifiers, periodically poled lithium niobate (PPLN) [31], silicon [32], soft glass [33] and using opto-electronic devices [34].…”
Section: Progress In Optical Phase Conjugation Systemsmentioning
confidence: 99%